Nuclear Structure, Size Regulation, and Role in Cell Migration - Yuhao Li; Shanghao Ge; Jiayi Liu; Deseng Sun; Yang Xi; Pan Chen (Cells)
The nucleus serves as a pivotal regulatory and control hub in the cell, governing numerous aspects of cellular functions, including DNA replication, transcription, and RNA processing. Therefore, any deviations in nuclear morphology, structure, or organization can strongly affect cellular activities. In this review, we provide an updated perspective on the structure and function of nuclear components, focusing on the linker of nucleoskeleton and cytoskeleton complex, the nuclear envelope, the nuclear lamina, and chromatin. Additionally, nuclear size should be considered a fundamental parameter for the cellular state. Its regulation is tightly linked to environmental changes, development, and various diseases, including cancer. Hence, we also provide a concise overview of different mechanisms by which nuclear size is determined, the emerging role of the nucleus as a mechanical sensor, and the implications of altered nuclear morphology on the physiology of diseased cells.